An ingredient co-occurrence network gives insight into e-liquid flavor complexity - Jeroen L. A. Pennings; Ina M. Hellmich; Sanne Boesveldt; Reinskje Talhout (Tobacco Induced Diseases)
Introduction Part of the appeal of e-cigarettes lies in their available flavors. To achieve attractive flavors, e-liquids contain many different flavoring agents, which allow many flavoring combinations. To advance our knowledge of e-liquid flavors and compositions and to evaluate the effect of legislation, we determined whether there are ingredient combinations that are frequently used together.